Analisis Faktor Internal, Pencahayaan, Kelembapan dan Suhu Rumah dengan Kejadian Tuberkulosis - Nurjannah, Siti; Yuantari, MG. Catur (Universitas Faletehan, 2024)
Tuberculosis cases in Semarang City were ranked sixth with the highest number of cases in Central Java, Indonesia. The aim of this research was to determine the relationship between internal factors, lighting, humidity and temperature with the incidence of tuberculosis. The type of research conducted was analytical observational quantitative research with a case-control approach. The number of samples of 104 respondents was selected using accidental sampling techniques and inclusion criteria. The data collection techniques carried out were secondary data collection, preliminary surveys, observations and interviews. The instruments included questionnaires, Lux Meter and Hygrometer. The analysis technique used a chi-square statistical test. This study found that there was a relationship between gender variables (OR 0.257; 95%CI; 0.110-0.598), education level, marital status (OR 0.229; 95%CI; 0.90-0.582), lighting (OR 0.099; 95%CI; 0.40-0.244), humidity (OR 0.082; 95%CI; 0.029-0.226), and bedding drying habits (OR 9.553; 95%CI; 3.727-24.487) with the incidence of tuberculosis in North Semarang District. The variables of income level, employment status, and temperature had nothing to do with the incidence of tuberculosis in North Semarang District.